Programação linear aplicada a estatística - Jesus, Alan Henrique de (2017)
Determine probabilities for events where we have few information or intervals for probabilities is not so simple. For this we will develop concepts of linear programming, which allows us to solve, in a certain way, the problem of determine a probability for an event of interest, but not always in a unique way. We will present some classic examples of statistics, such as: The Monty Hall Problem and De La Probabilité Des Témoignages. In addition, we will discuss the problem of pricing a call option, where we will use linear programming to solve them.